Sociology - Giddens, Anthony, 1938- (Polity Press, 1997)
A comprehensive overview of the discipline of sociology. This introductory text by an author of international reputation covers the following themes: the relation between the social and the personal, the globalisation of social life and the world in change, and the impact of change on social behaviour and patterns. The text is both comparative and historical in its orientation and deals with gender issues.